Triglyceride to High Density Lipoprotein-Cholesterol Ratio as Predictor of Cardiometabolic Risk among Doctors (Journal of Enam Medical College, 2019)
Background: Cardiometabolic risk indicates high risk of cardiovascular disease for a person. Obesity, hyperglycemia, hypertension, insulin resistance and dyslipidemia are the contributing factors for cardiometabolic risk.Objective: This cross sectional analytical study was conducted to evaluate triglyceride to high density lipoprotein-cholesterol ratio as predictor of cardiometabolic risk among doctors and to compare the risk between male and female doctors.Results: One hundred ninety five doctors were enrolled in this study. According to triglyceride to high density lipoprotein-cholesterol ratio 63.5% doctors have cardiometabolic risk in which male and female doctors were 66.3% and 57.5% respectively. The prevalence was apparently higher in male doctors than in female doctors. Receiver operating characteristic curve analysis on the basis of triglyceride to high density lipoprotein-cholesterol ratio at a cutoff value ≥3.0 showed area under curve 0.81 (p value=0.000) with sensitivity 72.3% and specificity 75.8%.Conclusion: It may be concluded from this study that triglyceride to high density lipoprotein-cholesterol ratio is a good predictor of cardiometabolic risk among doctors.J Enam Med Col 2019; 9(3): 181-184